Preparation and Performance Testing of Oxygen Ion Sensing Electrode in Chloride Molten Salt System - XIAO Yiqun1, LI Bin1, LIU Sijing1, 2, YAO Benlin1, YE Guoan1, HE Hui1 (Yuanzineng kexue jishu)
The aim of this study is to develop yttria-stabilized zirconia (YSZ) oxygen ion sensing electrode (referred to as YSZ electrode) for the accurate and real-time monitoring of oxygen ion concentration in high-temperature chloride molten salt systems. Such systems are widely applied in processes such as dry processing of spent nuclear fuel, metal extraction, and molten salt energy storage due to their excellent thermal stability, electrochemical stability, and low vapor pressure. The role of oxygen ions is critical during the electrochemical reduction of uranium-plutonium mixed oxide fuels, where oxygen ions migrate to the anode and oxidize into oxygen gas. High oxygen ion concentrations can lead to platinum corrosion, while low concentrations may cause platinum dissolution. To address these challenges, it is essential to develop in-situ methods for oxygen ion detection in molten salt systems. YSZ electrodes were fabricated using a tubular YSZ membrane filled with reference molten salt containing AgCl and Li2CO3. The electrodes were designed to function in high-temperature environments, featuring robust sealing and miniaturized structures to facilitate usage in confined spaces. The electrodes were tested in LiCl-KCl molten salt under various conditions, including changes in temperature, oxygen ion concentration, and gas flow rates. Electrochemical measurements were performed using a potentiostat to evaluate the response, stability, reproducibility, and parallelism of the electrodes. The performance of the reference electrode was also verified to ensure accuracy and reliability. Additionally, system designs ensured compatibility with high-temperature dynamic environments. The results show that YSZ electrodes are highly sensitive to temperature and oxygen ion concentration variations, providing accurate real-time monitoring of oxygen ion changes. Stability tests indicate that the electrodes could operate reliably under low and high oxygen ion concentrations, with potential fluctuations of ±10 mV and ±4 mV, respectively. Reproducibility was validated through single and multiple experiments, with consistent potential measurements across different trials. Parallelism tests demonstrate that the output potentials of different electrodes are consistent under identical conditions, and the potential values are linearly related to logarithmic concentration of oxygen ion (pO2−), with R2 exceeding 0.996. Furthermore, response time tests show that the electrodes quickly adapt to dynamic changes in oxygen ion concentration, and their performance remains stable over long durations. In summary, YSZ electrodes have demonstrated excellent performance in high-temperature chloride molten salt environments. They provide reliable, accurate, and stable measurement of oxygen ion concentration, making them suitable for dry processing of oxide fuels, electrochemical reduction, and other high-temperature processes.